The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1442-9071.2011.02523.x
|View full text |Cite
|
Sign up to set email alerts
|

Vogt-Koyanagi-Harada disease presenting as acute angle closure glaucoma at onset

Abstract: VKH disease presenting with a bilateral increased IOP mostly occurs in older women. The strikingly decreased visual acuity associated with mild to moderate increased IOP is a clue to the diagnosis. The increased IOP responded well to corticosteroids but not to anti-glaucoma treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 20 publications
0
38
0
1
Order By: Relevance
“…Inflammatory uveal effusions, such as those secondary to posterior scleritis and VKH syndrome are effectively managed with systemic corticosteroids and steroid-sparing drugs such as methotrexate and azathioprine. 7 Drug-induced uveal effusions gradually resolve on cessation of the causative drug in consultation with the patient's physician. Topical corticosteroids help reduce ciliary inflammation in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory uveal effusions, such as those secondary to posterior scleritis and VKH syndrome are effectively managed with systemic corticosteroids and steroid-sparing drugs such as methotrexate and azathioprine. 7 Drug-induced uveal effusions gradually resolve on cessation of the causative drug in consultation with the patient's physician. Topical corticosteroids help reduce ciliary inflammation in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Mansouri and Ravinet reported that iridoplasty was successful in the treatment of a uveitic eye with acute angle closure which was resistant to medical treatment and repeated laser iridotomies (Yang et al, 2011). Besides this isolated report, there is little additional evidence for the efficacy of iridoplasty in the treatment of angle closure in eyes with uveitis, and it is often not possible to mechanically widen the angle with laser burns to the iris in uveitic eyes (Kok and Barton, 2002).…”
Section: Specific Treatment For Angle Closurementioning
confidence: 95%
“…Detachment of the ciliary body occurs in eyes with severe ocular inflammation and has been associated with posterior scleritis (Heinz et al, 2013), Vogt-KayanagiHarada disease (Kishi et al, 1996;Yang et al, 2011;Yao et al, 2013), pars planitis, and uveal effusion syndrome (Saari, 1976). These patients can present with an acute increase in IOP (Kishi et al, 1996;Yamamura et al, 2008;Yang et al, 2011;Yao et al, 2013) and are easily misdiagnosed as acute primary angle closure.…”
Section: Anterior Displacement Of the Iris-lens Diaphragmmentioning
confidence: 97%
See 2 more Smart Citations